Analysis of Local Government Responsiveness Capacity in Higher Education from the Perspective of Public Policy - Tin Amalia; Gesit Yudha (Prodi Tata Negara (Siyasah) IAIN Langsa, 2026)
This study examines the responsiveness capacity of local governments in higher education policy from a public policy perspective within decentralized governance systems. The research is motivated by the growing demand for local governments to move beyond administrative compliance toward adaptive and collaborative governance capable of addressing complex educational challenges. Despite the strategic importance of higher education for regional innovation, labor market alignment, and social mobility, studies on local government responsiveness have predominantly focused on basic public services, leaving higher education underexplored. This study employs a Systematic Literature Review (SLR) methodology by analyzing peer-reviewed articles published between 2013 and 2024 sourced from Scopus, Web of Science, and Google Scholar. The findings reveal that responsiveness is influenced by institutional capacity, leadership quality, stakeholder engagement, intergovernmental coordination, fiscal autonomy, and digital governance infrastructure. The study further proposes a “Hybrid Responsiveness” model integrating collaborative governance and adaptive governance approaches to explain how local governments balance administrative obligations with strategic regional innovation. This research contributes to practical standpoint, it provides a policy-oriented framework that emphasizes institutional strengthening, fiscal reform to support higher education initiatives, and multi-stakeholder coordination mechanisms, thereby enabling local governments to play a more effective and responsive role in fostering inclusive and sustainable higher education development.